Physical, Chemical and Biological Effects on Soil Bacterial Dynamics in Microscale Models - König, Sara; Vogel, Hans-Jörg; Harms, Hauke; Worrich, Anja (Frontiers in Ecology and Evolution, 2020)
Soil is populated by highly diverse microbial communities mediating important processes and functions. The distribution of microbes, however, is neither uniform nor random. Instead, it is dictated by physical, chemical and biological processes and conditions and varying over small spatial and temporal scales. The feedbacks between these processes make the soil-microbe complex a self-organizing system capable of adapting to the continuously changing conditions mainly driven by the highly fluctuating water content. For making meaningful predictions on the spatiotemporal dynamics of soil microbes and their functions, we need to integrate knowledge from physics, chemistry and biology in our modeling approaches. Here, we review modeling studies with a focus on spatiotemporal dynamics of bacteria and bacterial functions in soil microhabitats. We compare these studies along four dimensions: specific aim, model type (individual-based, population-based), scale, and considered physical, chemical, biological processes and aspects. A special emphasis is laid on modeling approaches considering processes and aspects influencing the spatial distribution of bacteria such as motility, vector-based dispersal and biofilm formation. This includes factors like soil structure, carbon and oxygen gradients, temporal variations in hydration conditions or anthropogenic disturbance events. By assessing the importance of different microscale bacterial processes, this review should contribute to the ongoing discussion on challenges related to the upscaling from the microscopic via the profile to the landscape scale. Recent technical advances to observe bacteria in soils or soil-like environments combined with multidisciplinary collaborations will help to shed light on currently understudied physical, chemical and biological interactions in the soil-microbe complex.